Revivalism of the Tarekat Naqsyabandiyah in Changing the Local Political Landscape of Rokan Hulu, Indonesia in Post-New Order - Hidayati, Mega; Handoko, Tito (FIKRAH, 2021)
Changes in Indonesia's socio-political require Islamic organizations to adapt to these changes, some of them have managed to survive and exist and died. Revivalism in Islam is a demand from the long history of Islam's journey, which has crossed the geographical and cross-cultural boundaries of Islamic society. The survival and death of the Islamic movement is highly dependent on the ability of Muslims adapts to the socio-political landscape, like the case of the Naqsyabandiyah Tarekat in Rokan Hulu-Riau, the existence of the movement survives because it is able to adapt to the socio-cultural system of the local community. This study shows there is an interaction between Islam and the culture of the community and influences each other.  The influence that occurs is sometimes positive and negative. The influence of Islam in the local socio-political landscape can be seen from the widespread use of Islamic symbols, as well as various local government policies that adopt Islamic values.